CHROMOENDOSCOPY IN DIAGNOSTICS OF PRECANCEROUS GASTRIC MUCOSA’S CONDITIONS AND LESIONS - Vernygorodskyi, S.V.; Degtiariova, L.; Shcherbakov, B.Yu. (World of Medicine and Biology, 2012)
The comparative endoscopic and pathomorphological analysis of macroscopic and microscopic changes of the gastric mucosa of 336 patients with precancerous conditions was performed. The advantage of chromoendoscopy over common endoscopy in diagnostics of precancerous lesions was revealed. The use of chromoendoscopy as screening test in patients with precancerous lesions was proposed.
Keywords: chromoendoscopy; precancerous lesions; gastric mucosa